THE ROLE OF ISLAMIC CULTURE COURSES IN MAINTAINING THE ISLAMIC IDENTITY: CASE STUDY OF FACULTY OF LANGUAGES AND TRANSLATION FEMALE STUDENTS AT KING KHALID UNIVERSITY - Metwally, Amal Abdelsattar; Alabdaly, Abeer Hussien; Bouziane, Meriem Attia (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
The present study is an interdisciplinary research that investigates the role of Islamic culture courses in maintaining the Islamic identity among the female students of the English department at King Khalid University. It is due to the significance of these courses that the researchers design this study to explore the extent to which the Islamic culture courses achieve the objectives envisaged by them. This study further explores the ability of these courses to confront the ideas of globalization and the new international order including the world’s economic, political, cultural and social ideologies. The study also investigates the need of such courses to enable the students of the English department to be prepared to study certain courses enrolled at the faculty of languages and translation (i.e. religious translation course). For this end, the students are requested to complete an online survey composed of closed-ended and open-ended questions on their perceptions about the Islamic culture courses and their significance. As such, the study adopts both quantitative and qualitative methods and ends up with suggesting certain recommendations towards improving the courses specifications and implementing the students’ special knowledge of the English language and culture in empowering them to present the disciplined Islamic concept and identity.